A Narrative Review of the Mediterranean Lifestyle and Its Role in Obesity Prevention and Management - Sotiria Laoutari; Efstratios Christodoulou; Antonios E. Koutelidakis (Obesities, 2025)
The Mediterranean lifestyle (ML), encompassing key elements such as the Mediterranean diet (MD), regular physical activity, social engagement, sleep-enhancing habits, sustainable food practices, including reducing food waste and opting for seasonal and local products, proximity to nature, and a focus on slow living, has garnered increasing interest for its potential in obesity prevention and management. This narrative review examines how these lifestyle characteristics may influence body weight regulation, metabolic health, and obesity-related outcomes. A thorough literature search was conducted to synthesize findings from epidemiological studies, clinical trials, and mechanistic research. Evidence suggests that adherence to the MD is linked to lower obesity rates, improved metabolic markers, and reduced risk of weight gain. Key components contributing to these effects include high fiber intake, healthy fatty acids from olive oil and nuts, and a balanced macronutrient profile that promotes satiety and reduces inflammation. Furthermore, lifestyle practices such as regular physical activity, strong social connections, and sleep-enhancing habits may further support weight management. Despite consistently favorable findings in observational studies, intervention trials reveal variability in individual responses, highlighting the need for personalized approaches. Future research should explore strategies to enhance adherence to the MD and investigate the interactions between diet, physical activity, and psychosocial factors in obesity prevention.